Collaborative teaching IMR652: sharing session featuring Sarawak Energy Berhad / Suhaida Halamy and Nurfaizah Kamarudin - Halamy, Suhaida; Kamarudin, Nurfaizah (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
This semester, we delve into the fascinating world of Management of Business Records (IMR652), a servicing subject to bachelor degree students from the Faculty of Business and Management. The students enrolled in this course come from three different degree programs: BA242 (Finance), BA240 (Marketing), and BA232 (Office System Management). Guiding them through this subject are four esteemed lecturers from the School of Information Science: Suhaida Halamy, Nurfaizah Kamarudin, Sharin Sulaiman, and Suriani Jack.